GC-MS analysis of bioactive compounds in ethanolic extract on different parts of Ziziphus mauritiana - LARBENNO PAULOI; RAFIDAH MD SALIM; LIEW KANG CHIANG; MURNI SUNDANG; NOR AZIZUN RUSDI; MANDY MAID; SHIRLEY MARYLINDA BAKANSING; JANSHAH MOKTAR (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Pauloi L, Salmim RM, Chiang LK, Sundang M, Rusdi NA, Maid M, Bakansing SM, Moktar J. 2024. GC-MS analysis of bioactive compounds in ethanolic extract on different parts of Ziziphus mauritiana. Biodiversitas 25: 3442-3453. Ziziphus mauritiana Lam., a tropical fruit-bearing tree commonly known as Bidara tree in Malaysia, has a long and rich history of use in traditional medicine. Cultures across the globe have utilized various parts of the plant, including its leaves, bark, fruit, and roots, to address a wide range of health issues, such as digestive disorders, skin conditions, and inflammatory ailments. This study aimed to comprehensively analyze the bioactive compounds present in different parts of Z. mauritiana using Gas Chromatography-Mass Spectrometry. Ethanolic extracts were prepared from the leaves, bark, stem, root, and fruit of the plant, and their chemical compositions were meticulously analyzed. The GC-MS analysis revealed a diverse array of bioactive chemicals belonging to various chemical classes, including organic acids, esters, silanes, and thiodipropionates. Notably, many of these identified compounds have demonstrated promising antibacterial, antioxidant, anti-inflammatory, and anticancer properties in previous scientific studies. The presence of these bioactive substances provides scientific support for the traditional medicinal uses of Z. mauritiana and underscores its potential as a valuable source for developing novel therapeutic agents. Further research is warranted to fully elucidate the individual bioactivities and potential synergistic effects of these compounds, paving the way for harnessing the full therapeutic potential of Z. mauritiana for improving human health and well-being.